A Rapidly Adaptable Management System. Issue 5 (September 2015) - Toussaint, John S.
Abstract : A s healthcare organizations nationwide are compelled to move from volume‐based payments to a value‐based system, one thing has become painfully clear: Most of these organizations are not equipped for flexibility. We cannot change at the required rate. One CEO told me recently that we need a rapid adaptability system and we don't have one. One problem is that healthcare leaders are typically managing dozens, even hundreds, of initiatives. Few of these projects are delivering better value for patients and most rarely lead to sustainable change. A new unified management system is needed. After years of studying the transformation efforts of more than 160 healthcare organizations in 16 countries, I have found that a framework exists for a rapid adaptability system. This framework is a daily management system that requires fundamental change at both the frontline and leadership levels. This column will address the core elements of this management system.